1655 Va. Acts 401, Act 12 - (:unkn) unknown (General Publisher, 1655)
What persons or persons soever shall, after publication hereof, shoot any guns at drinking (marriages and funerals only excepted) that such person or persons so offending shall forfeit 100 lb. of tobacco to be levied by distress in case of refusal and to be disposed of by the militia in ammunition towards a magazine for the county where the offence shall be committed.
--
Keywords: DISCHARGE